Those who hold Bastogne the true story of the Soldiers and Civilians who fought in the biggest battle of the bulge - Schrijvers, Peter 1963- (Yale University Press, 2014)
A new telling of the brutal siege of Bastogne, where vastly outnumbered American forces held off a savage German onslaught and sealed the fate of the Third Reich